Defining major trauma using the 2008 Abbreviated Injury Scale - Palmer, Cameron S; Gabbe, Belinda J; Cameron, Peter A (Injury, 2016)
The Injury Severity Score (ISS) is the most ubiquitous summary score derived from Abbreviated Injury Scale (AIS) data. It is frequently used to classify patients as ‘major trauma’ using a threshold of ISS >15. However, it is not known whether this is still appropriate, given the changes which have been made to the AIS codeset since this threshold was first used. This study aimed to identify appropriate ISS and New Injury Severity Score (NISS) thresholds for use with the 2008 AIS (AIS08) which predict mortality and in-hospital resource use comparably to ISS >15 using AIS98. Data from 37,760 patients in a state trauma registry were retrieved and reviewed. AIS data coded using the 1998 AIS (AIS98) were mapped to AIS08. ISS and NISS were calculated, and their effects on patient classification compared. The ability of selected ISS and NISS thresholds to predict mortality or high-level in-hospital resource use (the need for ICU or urgent surgery) was assessed. An ISS >12 using AIS08 was similar to an ISS >15 using AIS98 in terms of both the number of patients classified major trauma, and overall major trauma mortality. A 10% mortality level was only seen for ISS 25 or greater. A NISS >15 performed similarly to both of these ISS thresholds. However, the AIS08-based ISS >12 threshold correctly classified significantly more patients than a NISS >15 threshold for all three severity measures assessed. When coding injuries using AIS08, an ISS >12 appears to function similarly to an ISS >15 in AIS98 for the purposes of identifying a population with an elevated risk of death after injury. Where mortality is a primary outcome of trauma monitoring, an ISS >12 threshold could be adopted to identify major trauma patients. Level II evidence—diagnostic tests and criteria.